Isothermal and isovolumetric process of CO2 adsorption on nitrogen-doped biochar: Equilibrium and non-equilibrium states - Geng, Yuhan; Du, Yarong; Guo, Tianxiang; Zhang, Yonghe; Bedane, Alemayehu Hailu; Ren, Peng (Case studies in thermal engineering, 2023)
In order to reveal the thermodynamic properties of CO2 adsorption on a promising nitrogen-doped biochar under isothermal and isovolumetric conditions, the adsorption isotherms based on 391 data points were experimentally obtained to investigate the mass and energy transfer process during CO2 adsorption by combining with model analysis. Then a series of interesting phenomena were found by analyzing those thermodynamic parameters in the equilibrium and non-equilibrium states. The capacity of CO2 on the biochar non-linearly increases with an increase of the initial pressure and volume-mass ratio but the decrease of the adsorption temperature. It can be up to 7.6 mol/kg at 273 K and 100 kPa. The adsorption system exchanges the energy with the surrounding environment mainly by heat transfer. And the interfacial energy of the adsorbent can be affected by the adsorbate system in three parts: pressure change from gas phase, molecular force from adsorbed phase and heat transfer. Then the conditions with low adsorption temperature, high initial pressure and large volume-mass ratio can provide a strong driving force for CO2 adsorption. These phenomena that have not been reported before will help us get a better technical process for CO2 capture. [Display omitted]